Feedlot performance of Charolais steers finished with different body weights - Restle, João; Keplin, Luis Antonio da Silveira; Vaz, Fabiano Nunes (Pesquisa Agropecuaria Brasileira, 1997)
The objective of the experiment was to evaluate the feedlot performance, average daily gain, feed consumption and feed conversion, of steers finished with different body weights. Eighteen Charolais steers, 30 months old, and initial weight of 297.0 kg±11.5 kg were used. The steers were slaughtered when the group average live weight reached 421.0 kg±45.4 kg (T1), 461.0 kg±29.1 kg (T2) or 495.0 kg±17.8 kg (T3). The steers were fed with a 12% crude protein diet, containing 57% of concentrate and 43% of green chopped sugar cane. A complete randomized design was used. Feed consumption was similar for the three treatments. However, feed consumption per 100 kg of live weight decreased as slaughter weight increased. Average daily gain of the steers was 1.12 kg±.05 kg, 1.17 kg±.12 kg and 1.05 kg±.09 kg, for T1, T2 and T3, respectively. Feed conversion was similar (P>.1696) for the three treatments. Subcutaneous fat was 2.4 mm±1.0 mm, 2.6 mm±1.8 mm and 5.4 mm±1.0 mm (P<.0022), respectively. The period for steers to reach the final weight was 110, 145 and 184 days, respectively.